Efektivitas Simulasi Pelatihan Bantuan Hidup Dasar (BHD) Terhadap Peningkatan Pengetahuan dan Motivasi Tentang Penanganan Kejadian Kecelakaan Lalu Lintas (KLL) pada Tukang Ojek - Djunizar Djamaludin; Eka Yudha Chrisanto; Lisa Yuliana Sari (Universitas Malahayati Lampung, 2021)
ABSTRACT: THE EFFECTIVENESS OF BASIC LIFE SUPPORT (BLS) TRAINING ON INCREASING KNOWLEDGE AND MOTIVATION OF TRAFFIC ACCIDENTS HANDLING IN MOTORCYCLE TAXI DRIVERS Introduction: Motorcycle taxi drivers are travelers who are often exposed to traffic accidents, where many motorcycle taxi drivers do activities on the streets such as waiting for orders, receiving orders and placing orders. Online motorcycle taxi providers moreover never provided basic life support training for online motorcycle taxi drivers. Factors of work accidents, work fatigue, poor sleep quality and the behavior of motorcycle taxi drivers that cause traffic accidents.Purpose: This study to determine the effectiveness of the basic life support (BLS) training on increasing knowledge and motivation traffic accidents handling in motorcycle taxi drivers at Bumisari Village, Natar District in 2021.Method: This study used a quasy experimental method of pre and post design. The subject of the research were the motorcycle drivers in the city of Natar, Lampung Selatan both the motorcycle driver's base and the online motorcycle drivers. Total 30 participants were requireted with purposive sampling. This research was using knowledge and motivaton questionnairs. Analysis bivariate were tested using paired t test and independent t-test using t-dependent test.Result: The average knowledge and motivation before being given a simulation of basic life support training (BLS) on handling traffic accidents on motorcycle taxi drivers, the mean of knowledge is 4.13 and the mean of motivation is 30.67. While online motorcycle taxi drivers have an average value before being given a BLS training simulation, namely the mean knowledge of 3.93 and the mean motivation of 29.40. The average knowledge and motivation after being given a simulation of basic life support (BLS) training on handling traffic accidents on motorcycle taxi drivers, the mean of knowledge is 8.93 and the mean of motivation is 60.00. Meanwhile, online motorcycle taxi drivers have an average value after being given a BLS training simulation, namely the mean knowledge is 8.73 and the mean motivation is 66.53. The results of bivariate data analysis using the t-test dependent test obtained p-value 0.000 0.05, it can be concluded that there is an effectiveness of basic life support training (BLS) simulation on increasing knowledge and motivation about handling traffic accidents (KLL) in motorcycle taxi drivers in Bumisari Village, Natar District in 2021 Conclusion: It is hoped that there will be increased learning about health promotion methods regarding basic life support (BHD) targeted at the community, especially motorcycle taxi drivers in Bumisari Village, Natar District. Keywords : Basic Life Support (BLS) Simulation, Knowledge, Motivation INTISARI: EFEKTIVITAS PELATIHAN BANTUAN HIDUP DASAR (BHD) TERHADAP PENINGKATAN PENGETAHUAN DAN MOTIVASI PENANGANAN KECELAKAAN LALU LINTAS PADA PENGEMUDI TAKSI SEPEDA MOTOR Latar Belakang: Tukang ojek merupakan pelaku perjalanan yang sering terpapar dengan kecelakaan lalu lintas, dimana aktifitas tukang ojek banyak dilakukan dijalanan seperti menunggu orderan, menerima orderan dan melakukan orderan. Provider ojek online juga tidak pernah menyediakan pelatihan pertolongan pertama pada kecelakaan pada pengemudi ojek online. Faktor kecelakaan kerja, kelelahan kerja, kualitas tidur yang buruk dan perilaku tukang ojek berakibat terjadinya kecelakaan lalu lintas.Tujuan: Diketahuinya efektivitas pelatihan bantuan hidup dasar (BHD) terhadap peningkatan pengetahuan dan motivasi tentang penanganan kejadian kecelakaan lalu lintas (KLL) pada tukang ojek di Desa Bumisari Kecamatan Natar Tahun 2021.Metode Penelitian: Penelitian ini menggunakan metode quasi eksperimental dengan pre and post design. Subyek penelitian ini adalah para tukang ojek di Kota Natar, Lampung Selatan baik tukang ojek pangkalan maupun ojek online. Jumlah tukang ojek yang bersedia mengikuti penelitian yaitu sebanyak 30 orang dengan purposive sampling. Penelitian ini menggunakan kuesioner pengetahuan dan motivasi. Analisis bivariat diuji dengan menggunakan uji t berpasangan dan uji t independenHasil : Rata-rata pengetahuan dan motivasi sebelum diberi simulasi pelatihan bantuan hidup dasar (BHD) tentang penanganan kejadian kecelakaan lalu lintas (KLL) pada tukang ojek pangkalan mean pengetahuan 4,13 dan mean motivasi 30,67. Sedangkan pada tukang ojek online terdapat nilai rata-rata sebelum diberi simulasi pelatihan BHD yaitu mean pengetahuan 3,93 dan mean motivasi 29,40 Rata-rata pengetahuan dan motivasi sesudah diberi simulasi pelatihan bantuan hidup dasar (BHD) tentang penanganan kejadian kecelakaan lalu lintas (KLL) pada tukang ojek pangkalan mean pengetahuan 8,93 dan mean motivasi 60,00. Sedangkan pada tukang ojek online terdapat nilai rata-rata sesudah diberikan simulasi pelatihan BHD yaitu mean pengetahuan 8,73 dan mean motivasi 66,53. Hasil analisa data bivariat menggunakan uji dependen t-tes didapat nilai p-value 0,000 0,05 maka dapat ditarik kesimpulan bahwa terdapat efektivitas simulasi pelatihan bantuan hidup dasar (BHD) terhadap peningkatan pengetahuan dan motivasi tentang penanganan kejadian kecelakaan lalu lintas (KLL) pada tukang ojek di Desa Bumisari Kecamatan Natar Tahun 2021.Kesimpulan: Diharapkan dapat mengadakan peningkatan pembelajaran tentang metode promosi kesehatan mengenai bantuan hidup dasar (BHD) yang ditargetkan kepada masyarakat khususnya Tukang Ojek di Desa Bumisari Kecamatan Natar. Kata Kunci: Simulasi Bantuan Hidup Dasar (BHD), Pengetahuan, Motivasi